A method for treating domestic sludge and/or industrial sludge and/or waste biomass and an apparatus used to treat the domestic sludge and/or industrial sludge and/or waste biomass - Idris, Azni; Mohd Salleh, Mohamad Amran (2013)
The present method for treating domestic sludge and/or industrial sludge and/or waste biomass, wherein the method involves the steps of (a) adding carbon particles into the domestic sludge and/or industrial sludge and/or biomass to produce a blend of the domestic sludge, industrial sludge and/or biomass and carbon particles and (b) heating the blend using a microwave heating at 2.45GHz magnetron unit to achieve a temperature range between 350 to 600 for duration of 15 to 60 minutes to produce syngas, bio-oil and biochar. Also provided is an apparatus (10) for treating domestic sludge and/or industrial sludge and/or waste biomass using the method. The apparatus (10) consists of a sludge mixing chamber (12), a microwave heating chamber (14), a product storage tank, a cooling condenser and an electricity generation unit.